2022
DOI: 10.7150/thno.67409
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteogenomics characterizes the CD44 splicing code associated with bladder cancer invasion

Abstract: Rationale: Bladder cancer (BC) management demands the introduction of novel molecular targets for precision medicine. Cell surface glycoprotein CD44 has been widely studied as a potential biomarker of BC aggressiveness and cancer stem cells. However, significant alternative splicing and multiple glycosylation generate a myriad of glycoproteoforms with potentially distinct functional roles. The lack of tools for precise molecular characterization has led to conflicting results, delaying clinical appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…1. Previous studies reported that sTn of integrin β1 disorders the integrin-associated signaling, which in turn alters the morphology and behaviors (adhesion and migration) of breast cancer cells 37,38 ; sTn modi ed CD44 is strongly associated with malignant phenotypes of colorectal, gastric, and prostate cancers [39][40][41] . 2.…”
Section: Discussionmentioning
confidence: 99%
“…1. Previous studies reported that sTn of integrin β1 disorders the integrin-associated signaling, which in turn alters the morphology and behaviors (adhesion and migration) of breast cancer cells 37,38 ; sTn modi ed CD44 is strongly associated with malignant phenotypes of colorectal, gastric, and prostate cancers [39][40][41] . 2.…”
Section: Discussionmentioning
confidence: 99%
“…CD44 is a multifunctional protein involved in cell adhesion, cell-matrix adhesion, cell migration, leukocyte homing and activation, tumor invasion, and metastasis. CD44 expression has been positively correlated with tumor aggressiveness and the response of bladder cancer to radiation, as well as associated with drug-resistant phenotype and poor prognosis [115][116][117][118]. It has also been proven that CD44 O-glycosylation status regulates cancer aggressiveness [119].…”
Section: The Role Of Mucin Expression In Bladder Cancermentioning
confidence: 99%
“…Among STn antigen-expressing proteins, several integrins and cadherins, as well as CD44, MUC1, and MUC16, were identified [112,127]. Interestingly, overexpression of STn antigen has been shown to modulate CD44-mediated invasion and regulate oncogenic pathways governed by CD44 [118]. Moreover, there is a positive correlation between STn antigen expression and the higher proliferation index of BC cells based on p53 and Ki-67 biomarkers [132].…”
Section: The Role Of Tn and T Antigens In Bladder Cancermentioning
confidence: 99%
“…Our previous studies showed that CD47 antibody conjugated to a NIR fluorophore can be used for fluorescence imaging of BCa ( 71 , 72 ). CD44 is a cancer stem cell marker, which is highly expressed on the cell membrane of BCa and participates in cell adhesion, cell migration, tumor progression and metastasis ( 73 ). The results of the first human experiment showed that the fluorescence-guided imaging based on the NIR fluorescence probe targeting CD44v6 is a safe and effective method, which can improve the detection rate of BCa, and may enable complete resection to prevent recurrence ( 74 ).…”
Section: Erbt Combined With Enhanced Imaging Technologymentioning
confidence: 99%